Efficacy and safety of lomitapide in homozygous familial hypercholesterolaemia: the pan-European retrospective observational study. (31st December 2021) - D'Erasmo, Laura; Steward, Kim; Cefalù, Angelo Baldassare; Di Costanzo, Alessia; Boersma, Eric; Bini, Simone; Arca, Marcello; van Lennep, Jeanine Roeters; ,
Abstract: Aims: Lomitapide is a lipid-lowering agent indicated as an adjunct therapy for adult homozygous familial hypercholesterolaemia (HoFH). This study evaluated the medium-term effectiveness and safety of lomitapide in a large cohort of HoFH patients in Europe. Methods and results: In a multicentre retrospective, observational study including 75 HoFH patients treated with lomitapide in a real-world clinical setting from 9 European countries, low-density lipoprotein cholesterol (LDL-C) changes, adverse events (AEs), and major adverse cardiovascular events (MACE) were assessed. After a median 19 months (interquartile range 11–41 months) of treatment with a mean dosage of 20 mg of lomitapide. Low-density lipoprotein cholesterol decreased by 60%, from baseline 280.5 mg/dL (191.8–405.0 mg/dL) to 121.6 mg/dL (61.0–190.5 mg/dL). At the last visit, 32.0% of patients achieved LDL-C <100 mg/dL and 18.7% <70 mg/dL. At baseline, 38 HoFH patients were receiving LDL apheresis (LA), but after initiation of lomitapide 36.8% of patients discontinued LA. During follow-up, lomitapide was permanently interrupted in 13% of patients. Gastrointestinal AEs occurred in 40% and liver transaminases increased (3–5 × upper limits of normal) in 13% of patients. Among patients with liver ultrasound evaluation ( n = 45), a modest increase in hepatic steatosis was noted during treatment; however, liver stiffness measured by elastography in 30 of them remained within the normal range. Among HoFH patients exposed to lomitapide for at least 2 years, MACE incident rate was 7.4 per 1000 person-years in the 2 years after as compared to 21.2 per 1000 person-years before treatment with lomitapide. Conclusion: In this medium-term real-world experience, lomitapide proved to be very effective in reducing LDL-C in HoFH. Gastrointestinal AEs were common, but liver safety was reassuring with no sign of increased risk of liver fibrosis. A signal of cardiovascular protection was also observed.